THE INFLUENCE OF FAMILY KNOWLEDGE AND PATIENT PERCEPTION OF BPJS INPATIENT HEALTH POLICY ON THE DECISION TO UPGRADE AT HOSPITAL IN KEDIRI CITY - Dwi Kumala Sari; Laili Wulandari; Endra Widiyanto (Journal of Hospital Management and Services, 2025)
This study aims to measure the influence of family knowledge and patient perception on the decision to upgrade the inpatient class of BPJS participants at Gambiran Hospital, Kediri City. A quantitative research design with a cross sectional approach was used on 164 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed by multiple linear regression. The results showed that family knowledge and patient perception had a significant effect on the decision to upgrade, with p-values of 0.002 and 0.004, respectively. Patient perception had a greater influence (B = 0.099) than family knowledge (B = 0.018). It is recommended that hospitals hold socialization to improve family understanding and patient perception of the BPJS upgrade policy.